2014
DOI: 10.1590/1806-9282.60.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of morbidity: trends in healthy life expectancy of the elderly population

Abstract: Conflict of interest: noneObjective: to analyze the changes in life expectancy (LE) and disability-free life expectancy (DFLE) in São Paulo's elderly population to assess the occurrence of compression or expansion of morbidity, between 2000 and 2010. Methods: cross-sectional and population survey, based on official data for the city of São Paulo, Brazil, and data obtained from the Health, Well-Being and Aging Survey (SABE). Functional disability was defined as difficulty in performing at least one basic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
9
0
2
Order By: Relevance
“…Chilean older women expected to live a lower proportion of their lives without disability and a higher proportion with disabilities, compared to men. Similar findings have been reported in other countries by previous studies [38,40,58]. In 2009, LE with mild or severe disability was higher for women.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Chilean older women expected to live a lower proportion of their lives without disability and a higher proportion with disabilities, compared to men. Similar findings have been reported in other countries by previous studies [38,40,58]. In 2009, LE with mild or severe disability was higher for women.…”
Section: Plos Onesupporting
confidence: 91%
“…Disability-free life expectancy (DFLE) has been used to monitor health expectancies of the population in the United States [31,32] and Europe [33][34][35] over the past several decades. Several studies on DFLE including Latin American populations exist [36][37][38][39][40][41][42][43][44][45], but only two studies have reported DFLE among Chilean older people, and they have focused on the population living in Santiago [46,47]. Estimations of LE in good SRH and DFLE at national level and comparisons over time are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although functional disability is not inherent in the aging process, 3 as individuals age, the chance of suffering injuries caused by accidents increases. 4 Studies show that such injuries are among the leading causes of death among older people and falls account for up to two thirds of accidents involving the elderly, representing one of the main predictors of morbidity and mortality. [5][6][7][8] Falls in elderly people may indicate the beginning of frailty or acute disease.…”
Section: Introductionmentioning
confidence: 99%
“…One of the aspects most evident in the aging process is the physical disabilities and degree of dependence of the elderly. While functional disability is not inherent to the aging process 14 , as an individual ages, the chances of suffering injuries from accidents increase 15 . Studies have shown that such injuries are among the main causes of death in elderly people and that falls represent up to two-thirds of accidents with the elderly, becoming one of the main predictors of morbidity and mortality 16,17 .…”
Section: Discussionmentioning
confidence: 99%